Selected issues on theory and methodology of the underground press - Roman, Wanda Krystyna (Knygotyra, 2024)
The main role of the press, published at any time, is to deliver information and form public opinion. The expectations are even higher regarding the underground press. The history of Poland has numerous references to the theory and methodology of the underground press. It starts from Polish uprisings at the end of the 18th century, goes through the occupation of Polish territories during World War I, includes illegal publications printed between the two World Wars, the underground press circulated during World War II, and ends with the underground press published in the People’s Republic of Poland (PRL). Because of the amount of underground press, comprising around 70% of total published press, one can try to look for generalizations regarding the role of the underground press, its place, and the aims it had on Polish soil over the last 200 years. The underground press was always published in parallel with the official press. The latter, however, was normally under a variety of pressures from the invaders or occupying authorities. This was either through repression during the II Republic of Poland or through preventative censorship during the People’s Republic of Poland. The underground press in Poland was always a fighting one. It came into existence under specific socio-political conditions and had to fulfill specific aims. The freedom of expression it offered was a counterbalance to the official newspapers. In the whole world’s press history, Polish secret and underground press, before and during the January Uprising of 1863, was a phenomenon never seen on such a scale before. Another example of such a phenomenon was the underground press published in occupied Polish territories during World War II. The underground press played a very important role in the Polish resistance movement. It was a source of information and also influenced the formation of public opinion, strengthening the will to live and fight. The press was, in that fight, like a sword and one of the main ways of communication through which the public learned about the requirements set for them in times of war. Every newspaper and magazine published during the occupation had very strong patriotic meaning too. They helped the public to survive with dignity by offering information, advice, warnings, and information on underground activities. As such, it should be critically verified. Questions about the underground press’s authenticity and credibility should be asked. The research of the press as a source of archived information requires the recreation of the history of a particular title and the establishment of the ways it was financed. Also important are the organizational links it had, availability of technical support, analysis of the editorial team and those who cooperated with it, the level of censorship, and the reconstruction of methods used for content selection and coverage.